METHODS OF DEVELOPING PEDAGOGICAL CREATIVITY OF FUTURE TEACHERS BASED ON A COMPETENT APPROACH - Bekchonova Shoira Bazarbaevna; Madjitova Kamola Azlar (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article highlights the possibility of creating a solid foundation for the development of pedagogical creativity of future teachers by applying a competency-based approach to teacher education programs.